A population‐based study of 92 clinically recognized risk factors for heart failure: co‐occurrence, prognosis and preventive potential. (26th January 2022) - Banerjee, Amitava; Pasea, Laura; Chung, Sheng‐Chia; Direk, Kenan; Asselbergs, Folkert W.; Grobbee, Diederick E.; Kotecha, Dipak; Anker, Stefan D.; Dyszynski, Tomasz; Tyl, Benoît; Denaxas, Spiros; Lumbers, R. Thomas; et al.
Abstract : Aims: Primary prevention strategies for heart failure (HF) have had limited success, possibly due to a wide range of underlying risk factors (RFs). Systematic evaluations of the prognostic burden and preventive potential across this wide range of risk factors are lacking. We aimed at estimating evidence, prevalence and co‐occurrence for primary prevention and impact on prognosis of RFs for incident HF. Methods and results: We systematically reviewed trials and observational evidence of primary HF prevention across 92 putative aetiologic RFs for HF identified from US and European clinical practice guidelines. We identified 170 885 individuals aged ≥30 years with incident HF from 1997 to 2017, using linked primary and secondary care UK electronic health records (EHR) and rule‐based phenotypes (ICD‐10, Read Version 2, OPCS‐4 procedure and medication codes) for each of 92 RFs. Only 10/92 factors had high quality observational evidence for association with incident HF; 7 had effective randomized controlled trial (RCT)‐based interventions for HF prevention (RCT‐HF), and 6 for cardiovascular disease prevention, but not HF (RCT‐CVD), and the remainder had no RCT‐based preventive interventions (RCT‐0). We were able to map 91/92 risk factors to EHR using 5961 terms, and 88/91 factors were represented by at least one patient. In the 5 years prior to HF diagnosis, 44.3% had ≥4 RFs. By RCT evidence, the most common RCT‐HF RFs were hypertension (48.5%), stable angina (34.9%), unstable angina (16.8%), myocardial infarction (15.8%), and diabetes (15.1%); RCT‐CVD RFs were smoking (46.4%) and obesity (29.9%); and RCT‐0 RFs were atrial arrhythmias (17.2%), cancer (16.5%), heavy alcohol intake (14.9%). Mortality at 1 year varied across all 91 factors (lowest: pregnancy‐related hormonal disorder 4.2%; highest: phaeochromocytoma 73.7%). Among new HF cases, 28.5% had no RCT‐HF RFs and 38.6% had no RCT‐CVD RFs. 15.6% had either no RF or only RCT‐0 RFs. Conclusion: One in six individuals with HF have no recorded RFs or RFs without trials. We provide a systematic map of primary preventive opportunities across a wide range of RFs for HF, demonstrating a high burden of co‐occurrence and the need for trials tackling multiple RFs. Abstract : A population‐based study of 92 clinically recognized risk factors for heart failure: co‐occurrence, prognosis and preventive potential.